2012
DOI: 10.1371/journal.pone.0036286
|View full text |Cite
|
Sign up to set email alerts
|

FcRn Overexpression in Transgenic Mice Results in Augmented APC Activity and Robust Immune Response with Increased Diversity of Induced Antibodies

Abstract: Our previous studies have shown that overexpression of bovine FcRn (bFcRn) in transgenic (Tg) mice leads to an increase in the humoral immune response, characterized by larger numbers of Ag-specific B cells and other immune cells in secondary lymphoid organs and higher levels of circulating Ag-specific antibodies (Abs). To gain additional insights into the mechanisms underlying this increase in humoral immune response, we further characterized the bFcRn Tg mice. Our Western blot analysis showed strong expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
39
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 45 publications
10
39
0
Order By: Relevance
“…[16][17][18][19] We previously reported the effects of FcRn overexpression accomplished by Tg modification in mice and rabbits. [20][21][22][23][24][25] These effects include quantitative as well as qualitative augmentation in the humoral immune response of these animals. More specifically, FcRn overexpression increases the number of Ag-specific B cells in the spleen generated in response to immunization, and increases antibody diversity.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[16][17][18][19] We previously reported the effects of FcRn overexpression accomplished by Tg modification in mice and rabbits. [20][21][22][23][24][25] These effects include quantitative as well as qualitative augmentation in the humoral immune response of these animals. More specifically, FcRn overexpression increases the number of Ag-specific B cells in the spleen generated in response to immunization, and increases antibody diversity.…”
Section: Resultsmentioning
confidence: 99%
“…Among the mechanisms that contribute to the boosted immune response, the augmented Ag-IgG IC presentation via professional APCs such as dendritic cells that express bFcRn seems to be especially important. 21,26 It is known that FcRn prevents degradation of circulating IgG (both Ag-specific and Ag-non-specific) and extends its half-life, but, because of the many more Ag-specific IgG producing B cells, the Ag-specific IgG fraction is disproportionally high relative to total IgG in these Tg animals. 20 Therefore, these FcRn Tg animals mount an enhanced immune response against epitopes that are otherwise weakly immunogenic or evade recognition by the immune system.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is not ideal to have to impose a correlation between the baseline IgG and FcRn concentration without some experimental evidence to support it. Experiments in transgenic animals with overexpression of FcRn have shown that they have higher levels of circulating IgG and improved immune function (46), suggesting higher levels of FcRn can result in higher plasma IgG levels. However, information on FcRn abundance and the variability within the human population and the correlation of the FcRn abundance with the steadystate IgG level is needed to further refine the minimal PBPK model.…”
Section: Discussionmentioning
confidence: 99%